2022
DOI: 10.1155/2022/4773179
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Application of Color Ultrasound in the Diagnosis of Gynecological Endocrine Disorders and Study of Ultrasonic Image Characteristics

Abstract: In order to study gynecological endocrine disorders, color ultrasound and image examination were used for in-depth study. After examining the clinical significance, research methods, strengthening treatment measures, and adjusting physical and mental health, the research and examination of endocrine disorders under ultrasound and ultrasound images are successfully analyzed. Endocrine is like a woman’s umbrella. When it is in harmony with the body, it will make women as beautiful as flowers. Once it becomes an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Color ultrasound is suitable for clinical applications because it poses little trauma, is convenient, and lacks radiation. [ 26 ] Color Doppler examination for pregnant women between 20 and 28 weeks of pregnancy is performed mainly to detect any cardiovascular abnormalities in the fetus. This information is then used to determine whether to induce labor surgically or to continue the pregnancy, which can help avoid fetal malformation to an extent and ensure the quality of the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…Color ultrasound is suitable for clinical applications because it poses little trauma, is convenient, and lacks radiation. [ 26 ] Color Doppler examination for pregnant women between 20 and 28 weeks of pregnancy is performed mainly to detect any cardiovascular abnormalities in the fetus. This information is then used to determine whether to induce labor surgically or to continue the pregnancy, which can help avoid fetal malformation to an extent and ensure the quality of the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…Значне зрушення у цьому питанні було досягнуто завдяки розробці та впровадженню у практику принципово нових способів отримання зображення. Одним із таких методів є ультразвукове дослідження (УЗД) або ехосонографії органів малого тазу [1,2,3,4]. Цей метод є методом вибору дитячої та підліткової гінекології.…”
Section: ключові слова: ехосонографія органів малого тазу аномальні м...unclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%